Distinção: efeito de trajetória social - Bianchini, Noemi (2011)
The area where this study is inserted is Education. The theme refers to the school learning and suffers clippings focusing on students-teachers who concluded the Normal Superior Course. After completion of the Master Course, concerns remained about some teachers-students education, and the first doctorate research questions arose. After all, how would it configure, really, what apparently could not be distinguished? Considering the hypothesis that the nuances observed in the interviews analysis with the teachersstudents at the Master Course and presented in Chapter 5, of the dissertation (Bianchini, 2005), were amplified / differentiated among the students-teachers components of the Doctorate, I considered that such nuances could be thought as peculiar constitutions of habitus and the school success would not be a talent result or merit for the studies. Using as a support for this study the Pierre Bourdieu Sociology, who favors us with important themes for studies in the educational sociology area, I highlighted the one who leads us to understand the social distinction production processes. Interviews were accomplished with two students-teachers who concluded the Normal Superior Course and received the Merit and Commendation Award at a graduation ceremony in two cities in São Paulo State country-side. The data analysis allowed us to understand the students-teachers practices as a practical sense product, as a "game sense" social and historically constructed and incorporated as habitus, as provisions constituted of specific capital, which allowed them to play the social and scholastic game with distinction and it may have been used, still, as a strategy in search of classification and / or reclassification in the social space in which they were inserted